Characterization of the Pore Network of a Cohesive Oxisol Through Morphological and Pore Complexity Analyses - Jocenei A. T. de Oliveira; Thaís N. Pessoa; José V. Gaspareto; Adolfo N. D. Posadas; André L. F. Lourenço; Paulo L. Libardi; Luiz F. Pires (Agriculture)
Cohesive Oxisols are a type of soil common in the Coastal Plateau in Brazil. These soils represent a challenge for agriculture and their study is fundamental to better land use. There have been a few studies on the porous system of cohesive soils on the micrometer scale. Our study aimed to provide a detailed analysis of the pore complexity of the cohesive horizon of a Brazilian Oxisol using 3D images (volumetric data reconstructed by 2D CT slices) and to correlate these parameters with soil physical–hydric attributes. For this purpose, images with two different resolutions were analyzed from multifractal, lacunarity, and entropy analyses. Additionally, a characterization of hydraulic properties was carried out based on a soil water retention curve (SWRC). No differences were observed between the resolutions for the different physical parameters analyzed. The lacunarity analysis showed a greater homogeneity of the pore system with pores grouped in clusters. The multifractal analysis showed fractal characteristics for the cohesive horizon, suggesting a more homogeneous pore distribution. The main results obtained from the SWRC showed a low available water content due to the predominance of ultramicropores. Overall, the results show a less complex pore system, indicating the presence of pores of small sizes, affecting the water retention and conduction through the soil.